Prevalence and Predictors of Palliative Care Utilization among Hospitalized Patients with Diffuse Large B-Cell Lymphoma. Issue 2 (April 2023) - Jackson, Inimfon; Etuk, Aniekeme; Jackson, Nsikak
Objective: Research has shown that palliative care improves the quality of life of cancer patients; however, there is no literature on specific factors that predict its use in diffuse large b-cell lymphoma (DLBCL) patients. Therefore, the prevalence of palliative care utilization and predictors of palliative care utilization among patients with DLBCL were examined.Methods: Data from the National Inpatient Sample (NIS) collected between 2016 to 2018 were used for all analyses. Multivariable logistic regression models were used to examine the predictors of palliative care utilization among hospitalized patients with DLBCL. Descriptive analyses were used to explore the overall prevalence of palliative care receipt in this population.Results: Of the 41, 789 hospitalizations, 7.1% of patients used palliative care during hospitalization, while 4.8% utilized palliative care and were discharged alive. DLBCL patients aged 70 and older had 1.3 times (95% CI: 1.14-1.41) higher odds of utilizing palliative care compared to those less than 70 years. Relative to Medicare/Medicaid patients, those with other types of insurance were 1.7 times (95% CI: 1.34-2.05) more likely to receive palliative care. Those who were either transferred to a facility/discharged with home health (AOR: 6.23; 95% CI: 5.21-7.44) or died during hospitalization (AOR: 45.17; 95% CI: 36.98-55.17) had higher odds of receiving palliative care when relative to those with a routine hospital discharge. Other associated factors were type of admission, length of stay, chemotherapy receipt, and number of comorbidities.Conclusions: The prevalence of palliative care utilization was low and factors predicting utilization in our population were identified. Our findings highlight the need to increase awareness among medical oncologists on the need to involve the palliative care team early in the management of hospitalized patients with DLBCL.